Circular Trajectory Reconstruction Uncovers Cell‐Cycle Progression and Regulatory Dynamics from Single‐Cell Hi‐C Maps. Issue 23 (30th September 2019) - Ye, Yusen; Gao, Lin; Zhang, Shihua
Abstract: Single‐cell Hi‐C technology is emerging and will provide unprecedented opportunities to elucidate chromosomal dynamics with high resolution. How to characterize pseudo time‐series of single cells using single‐cell Hi‐C maps is an essential and challenging topic. To this end, a powerful circular trajectory reconstruction tool CIRCLET is developed to resolve cell cycle phases of single cells by considering multiscale features of chromosomal architectures without specifying a starting cell. CIRCLET reveals its best superiority based on the combination of one feature set about global information and another two feature sets about local interactional information in terms of designed evaluation indexes and verification strategies from a collection of cell‐cycle Hi‐C maps of 1171 single cells. Further division of the reconstructed trajectory into 12 stages helps to accurately characterize the dynamics of chromosomal structures and explain the special regulatory events along cell‐cycle progression. Last but not the least, the reconstructed trajectory helps to uncover important regulatory genes related with dynamic substructures, providing a novel framework for discovering regulatory regions even cancer markers at single‐cell resolution. Abstract : CIRCLET first extracts multiscale features of chromosomal architectures for each cell, and then reconstructs a circular trajectory of single cells. Further division of the reconstructed trajectory helps to characterize the dynamics of chromosomal structures and uncover important regulatory genes along cell‐cycle progression. CIRCLET is the first tool for accurate reconstruction of a pseudotime trajectory based on single‐cell 3D genome maps.